Pemetaan Ekowisata Terumbu Karang Berbasis Geographic Information System (GIS) di Pulau Pahawang - Madany, Orista Ammar; Herison, Ahmad; Romdania, Yuda; Ashruri, A (Universitas Lampung, 2023)
AbstractCoral reef ecosystems are threatened with extinction. Along with the development of technology, the distribution of coral reefs can be reviewed only by looking at an information map. The purpose of this research is to map coral reef ecotourism on Pahawang Island. So that it is expected to provide information to the community and also island developers related to the condition of the coral reef ecosystem on Pahawang Island. The method used in map processing is sentinel 2A image data processing with the guided classification method in ArcGIS software, while the analysis method is descriptive, which describes the results of the coral reef cover map. The results of the analysis and discussion found that Geographic Information System (GIS) based remote sensing with processed sentinel 2A imagery is very helpful in the process of finding information on the distribution of coral reefs on Pahawang Island. Data processing in ArcGIS software using guided classification methods can be used in order to produce coral cover maps. The results of the coral reef distribution map have an area of 128.64 Ha. The conclusion is that Geographic Information System (GIS) based remote sensing with ArcGIS software can be used to produce coral cover maps. On Pahawang Island, the coral reef cover area of 128.64 Ha was obtained.